2010
DOI: 10.1093/her/cyq073
|View full text |Cite
|
Sign up to set email alerts
|

The impact of graphic cigarette warning labels and smoke-free law on health awareness and thoughts of quitting in Taiwan

Abstract: The present study evaluated the impact of Taiwan's graphic cigarette warning labels and smoke-free law on awareness of the health hazards of smoking and thoughts of quitting smoking. National representative samples of 1074 and 1094 people, respectively, were conducted successfully by telephone in July 2008 (pre-law) and March 2009 (post-law). Results reveal that the prevalence of thinking about the health hazards of smoking among smokers increased from 50.6% pre-law to 79.6% post-law, while the prevalence amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…However, the Taiwanese government passed the Tobacco Hazard Prevention Act in 1997, through which indoor places became partially smoke free. In 2002, the government started the Outpatient Smoking Cessation Services programme, and levied a health and welfare surcharge on each pack of cigarettes 63. Amendment of the Act in 2009 strengthened the legislation by extending smoke-free areas to almost all enclosed workplaces and public places, adding graphic health warnings to cigarette packages, and totally banning tobacco advertising, promotion, and sponsorship as recommended by the FCTC 63…”
Section: Discussionmentioning
confidence: 99%
“…However, the Taiwanese government passed the Tobacco Hazard Prevention Act in 1997, through which indoor places became partially smoke free. In 2002, the government started the Outpatient Smoking Cessation Services programme, and levied a health and welfare surcharge on each pack of cigarettes 63. Amendment of the Act in 2009 strengthened the legislation by extending smoke-free areas to almost all enclosed workplaces and public places, adding graphic health warnings to cigarette packages, and totally banning tobacco advertising, promotion, and sponsorship as recommended by the FCTC 63…”
Section: Discussionmentioning
confidence: 99%
“…The remaining participants who had smoked waterpipe at least once at some point in their lives, even one or two puffs, were classified as ever users. To assess responses to each health warning, participant were asked the question “to what extent do the following health warning labels motivate you to think about stopping or reducing your hookah smoking” (Chang et al 2011; Gravely et al 2014). Participants could choose one of the following responses: ‘not at all’, ‘somewhat’, and ‘very much’.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 The prevalence of cigarette smoking, alcohol drinking, and areca nut chewing in Taiwanese women is relatively low. 17 By contrast, our previous study has found that the prevalence of use of any substance was more than half (w53%) in Taiwanese healthy men who were from community residences and attended the hospitals for routine physical checkups. 18 To avoid the significant influence of substance use on the relationship between clinical biochemical factors and prediabetes, we only focused on women who did not have any habit of substance use in this study.…”
Section: Introductionmentioning
confidence: 79%